Acute Pseudomembran Candidiasis In A Patient With Osteogenic Sarcoma And Anemia - Zara Alviometha; Ade Puspa Sari; Siti Rusdiana Puspa Dewi (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2021)
Introduction: Acute pseudomembranous candidiasis is an opportunistic infection caused by the overgrowth of Candida spp. Candida spp can become pathogenic in a weak immune response. There is a clear relationship between oral candidiasis and patients with malignant disease (cancer) and hematological disorders, such as anemia. Anemia is a complication that often occurs in patients with malignancy. Purpose: This paper reports a case of acute pseudomembtane candidasis caused by osteogenic sarcoma and secondary anemia. Case presentation: A 12-year-old male patient was hospitalized for osteogenic sarcoma and anemia. Intraoral examination showed white plaque that could be wiped out on the tongue dorsum. Candida albicans was identified by oral microbial tests. Antifungal therapy was applied for 14 days and it showed improvement. Conclusion: The successful management of this patient involves control of predisposing factors, plaque control, and DHE.